2022
DOI: 10.21203/rs.3.rs-2321445/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field inoculation with arbuscular mycorrhizal fungi having contrasting life-history strategies differently affects tomato nutrient uptake and residue decomposition dynamics

Abstract: Purpose: In the scenario of an increased atmospheric CO2 concentration, nutrients are reduced in all vegetables. In this context, arbuscular mycorrhizal fungi (AMF) could enhance nutrient concentration in edible portions of plants, including tomato. However, field studies on tomato AMF inoculation are scarse. AMF species belonging to Gigasporaceae and Glomeraceae families known to vary in life-history strategies may determine differential effects on plant nutrient benefits and residue decomposition. Despite th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 126 publications
(113 reference statements)
1
2
0
Order By: Relevance
“…Our ndings are in accordance with previous results obtained on bread wheat genotypes and in sun ower, inoculated with the same AM fungal consortium in similar climatic conditions (Arcidiacono et al 2024;Marrassini et al 2024). Therefore, our data supports the low environmental and ecological impact of local AM fungal inoculants.…”
Section: Community Composition and Structure Of Amf In Barley Rootssupporting
confidence: 94%
See 1 more Smart Citation
“…Our ndings are in accordance with previous results obtained on bread wheat genotypes and in sun ower, inoculated with the same AM fungal consortium in similar climatic conditions (Arcidiacono et al 2024;Marrassini et al 2024). Therefore, our data supports the low environmental and ecological impact of local AM fungal inoculants.…”
Section: Community Composition and Structure Of Amf In Barley Rootssupporting
confidence: 94%
“…Therefore, as we hypothesized, under low soil fertility AM fungal colonization traits, such as the percentage of arbuscules, are key and consistent determinants of the productivity of barley. Similarly, in eld conditions, arbuscules were positively and strongly correlated with all functional traits of sun ower grown at low and high soil fertility (Arcidiacono et al 2024). The association between increased AM fungal root colonization and increased barley productivity is consistent with the results of meta-analytic works ( Moreover, the agronomic response of barley was driven also by changes in the structure of the AM fungal community, as highlighted in Fig.…”
Section: Modelling Barley Productivity Against Am Fungal Abundance An...mentioning
confidence: 91%
“…due to which spores kept multiplied in association with plants and remain in soil. Arcidiacono et al (2023) also reported preference of AM fungi upon tomato. Growth-promoting effect of AM fungi on cherry tomato were made by Tang (2022).…”
Section: Discussionmentioning
confidence: 87%